2015
DOI: 10.1142/s0192415x15500603
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of p38 MAPK in the Anticancer Activity of Cultivated Cordyceps militaris

Abstract: Cordyceps militaris is a traditional Chinese medicine frequently used for tonic and therapeutic purposes. Reports from our laboratory and others have demonstrated that extracts of the cultivated fruiting bodies of C. militaris (CM) exhibit a potent cytotoxic effect against many cancer cell lines, especially human leukemia cells. Here, we further investigated the underlying mechanism through which CM is cytotoxic to cancer cells. The CM-mediated induction of PARP cleavage and its related DNA damage signal (γH2A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…C . militaris exhibits anticancer, antioxidant, antiinflammatory, antihyperglycemic, and antimetastatic effects (Chou, Lai, Hong, et al, ; Huang, Lin, Mau, et al, ; S. Liu, Tang, Huang, et al, ). The immunomodulating activities of C .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C . militaris exhibits anticancer, antioxidant, antiinflammatory, antihyperglycemic, and antimetastatic effects (Chou, Lai, Hong, et al, ; Huang, Lin, Mau, et al, ; S. Liu, Tang, Huang, et al, ). The immunomodulating activities of C .…”
Section: Introductionmentioning
confidence: 99%
“…Liu, Kopparapu, Li, et al, 2017). Abbreviations: Con A, concanavalin A; IFN-γ, interferon-γ; IL, interleukin; MTX, methotrexate; NK, natural killer; TNF-α, tumor necrosis factor-α C. militaris exhibits anticancer, antioxidant, antiinflammatory, antihyperglycemic, and antimetastatic effects (Chou, Lai, Hong, et al, 2015;Huang, Lin, Mau, et al, 2015;S. Liu, Tang, Huang, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The activation of p38 and JNK can induce apoptosis but the activation of ERK1/2 can be an anti-apoptotic or pro-apoptotic agent depending on the cell properties [33]. It has been reported that CHM induced the apoptosis of tumor cells by activating p38, JNK or ERK MAPK pathways [34,35]. We found that CTPG up-regulated the phosphorylated levels of p38, JNK and ERK, suggesting that MAPK signaling pathway might be involved in the apoptosis of HCC cells induced by CTPG.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the encouraging effectiveness, few side effects and overwhelming resistance to drugs, C. sinensis has been increasingly utilized as an antitumor herb in Chinese medicine and an adjuvant of chemo‐ and radiotherapy for the treatment of cancers (Chen, Wang, Nie, & Marcone, 2013; Santos et al., 2018; Xie et al., 2018). Previous studies on the anticancer capacities of fermented C. sinensis have mainly focused on their water or organic extracts (Chou et al., 2015; Kubo et al., 2010, 2012). In contrast, the antitumor potency of the volatile oils was seldom evaluated.…”
Section: Introductionmentioning
confidence: 99%